2021
DOI: 10.14295/bds.2021.v24i4.2626
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Primary Molars Restored with Endocrowns Versus Zirconia Crowns (An in Vitro Study)

Abstract: Objective: This study aimed to assess the fracture resistance of primary molars restored with endocrowns compared to prefabricated zirconia crowns. Methods: Twelve sound, defect-free primary second molars were selected and divided into two groups: group I included 6 molars restored with zirconia crowns, while group II included 6 teeth restored with endocrowns. For both groups access cavity was prepared for the teeth to open pulp chamber. Fracture resistance of both groups was tested using a universal testing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In contrast, Sabbah and Kamel (18) compared the strength of primary molars with endocrown restorations to zirconia crowns that were already made. In comparison to Endocrown, Zirconia Crown demonstrated statistically substantially greater mean fracture resistance (P = 0.001).Compared to primary molars restored with endocrowns, pulpotomized teeth with Zirconia crowns shown considerably higher mean fracture resistance; nonetheless, both restorations demonstrated mean fracture resistance greater than the maximal biting force in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Sabbah and Kamel (18) compared the strength of primary molars with endocrown restorations to zirconia crowns that were already made. In comparison to Endocrown, Zirconia Crown demonstrated statistically substantially greater mean fracture resistance (P = 0.001).Compared to primary molars restored with endocrowns, pulpotomized teeth with Zirconia crowns shown considerably higher mean fracture resistance; nonetheless, both restorations demonstrated mean fracture resistance greater than the maximal biting force in children.…”
Section: Discussionmentioning
confidence: 99%
“…El Makawi and Khattab et al (1) revealed that compared to lithium disilicate endocrowns, Nusmile zirconia crowns had statistically significantly superior fracture resistance. Sabbah and Kamel (18) assessed the fracture resistance of primary molars restored with Endocrowns (ceram.x SphereTEC one universal, Dentsply Sirona, USA). El Makawi and Khattab (1) assessed the fracture resistance of primary molars restored with Endocrowns (IPS e.max Press/ Ivoclar Vivadent).…”
Section: Discussionmentioning
confidence: 99%
“…Its main characteristics include translucency, biocompatibility, high mechanical resistance, and color mimetics to obtain high aesthetic results [2]. Zirconium oxide ceramics (ZrO 2 , 3 rd generation) have been widely used in prosthetic dentistry, and the clinical success of restorations depends not only on esthetic or functional results but also on bond durability between dental tissues and prosthetic substrates [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%